Factors Affecting Competence of School Counselors in South Sulawesi - Pandang, Abdullah; Abimanyu, Soli; Mahmud, Alimuddin; Samad, Sulaiman (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
This article aims at exploring the profile of school counsellor’s competency in South Sulawesi, Indonesia, and factors that affected it. The study used quantitative approach, involving four independent variables, age, work experience, educational background, and professional certification experience of the school counsellor, and one dependent variable, the score of the competency test. The population of the study was 1949 school counsellors who took competency test administered by the Ministry of Education and Culture in 2015. There were 322 samples taken using proportional random sampling technique, representing school counsellors from SMP (junior high school), SMA (senior high school), and SMK (vocational schools). The result of the study showed that the average score of the competency test was still below the minimum standard set by the Government. The study also presented that there was a negative influence between age and the score, and positive influence between educational background and teacher certification program, and the results of competency test. Yet, it was found there was no significant influence between working experience and the results of competency test.